Ilegitimidad, alcoholismo y tuberculosis: explicaciones médicas de la mortalidad infantil. Santiago de Chile (1870-1912) - Pablo Chávez Zúñiga (Centre de Recherches sur les Mondes Américains, 2019)
This article analyzes the approaches of medical specialists dedicated to childhood, between the second half of the nineteenth century and the first decades of the twentieth century. Through publications in the press and titling reports, he explores the explanations of the causes of infant mortality in relation to a collection of scientific elements and a wide range of moral judgments, including the illegitimacy of birth, alcoholism and tuberculosis. After this analysis, it is concluded that up to the organization of pediatric medicine and the promulgation of the Law of the Children Invalid, they were adopted a series of arguments related to the culture of the time more than in the treatments of the diseases to try to reduce one of the highest rates worldwide.